2001
DOI: 10.1177/019251301022004007
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents and Grandparenting in a Rural Southern State

Abstract: Current social and demographic changes have drawn attention to the relationship between grandparents and grandchildren. This research examined grandparents and grandparenting in a rural southern state. One hundred fifty-eight grandparents were interviewed by telephone regarding their roles and relationships with their grandchildren and others along with the impact grandparenting had on their other activities. Results indicate that 60% of the sample had frequent contact with their grandchildren. A significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, there may be stronger family ties with paternal grandparents in some contexts, such as rural social environments. Researchers in the United States found that paternal grandparent–grandchild relationships in rural farm families feature a high degree of emotional closeness (King & Elder, 1995; King, Silverstein, Elder, Bengtson, & Conger, 2003; Spence, Black, Adams, & Crowther, 2001). The researchers interpreted this as a result of the nature of the work in farm families and the fact that most farm property is passed down to sons (King & Elder, 1995).…”
Section: Determinants Of Support Exchange Between Grandparents and Grmentioning
confidence: 99%
“…However, there may be stronger family ties with paternal grandparents in some contexts, such as rural social environments. Researchers in the United States found that paternal grandparent–grandchild relationships in rural farm families feature a high degree of emotional closeness (King & Elder, 1995; King, Silverstein, Elder, Bengtson, & Conger, 2003; Spence, Black, Adams, & Crowther, 2001). The researchers interpreted this as a result of the nature of the work in farm families and the fact that most farm property is passed down to sons (King & Elder, 1995).…”
Section: Determinants Of Support Exchange Between Grandparents and Grmentioning
confidence: 99%